TINJAUAN KEMAMPUAN KETERAMPILAN TEKNIK DASAR SEPAKBOLA PADA SISWA SSB RUMBAI PRATAMA PEKANBARU - Zulkarnain, Wawan; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research is the ability of basic soccer technique skills on SSB Rumbai Pratama still not fully good and correct. Heading, passing & stopping, dribbling and shooting is not right how to do it so the result is not maximal. This is allegedly because students of SSB Rumbai Pratama have not practiced and received a well-given exercise program. This study aims to determine the description of basic soccer skills skills skills in SSB Rumbai Pratama Pekanbaru students. Sampling technique is the total population (total sampling) SSB Rumbai Pratama Pekanbaru students, amounting to 18 people. This study uses the technique of achievement scale of T-score. Then, the test data using a test of the basic soccer skills skills measurement skills. Which is where the data obtained is changed into the form of T-score. Based on the results of research and data processing using statistical research procedures, it was obtained a recapitulation of T-score skills of basic soccer skills technique of SSB rumbai Pratama that is 40.66 on the frequency distribution range of 37 - 45 and categorized less.Keywords: The basic technique of football, heading, passing and stopping, dribbling. Shooting.